The Concept of Learners in the Framework of Educational Philosophy - Wakia, Nurul; Itin, Andi; Harisah, Afifuddin; Marjuni, Andi (DIDAKTIKA, 2025)
The concept of learners in education is often understood normatively and psychologically, without placing it within a complete philosophical framework. In fact, educational philosophy plays an important role in defining the essence of learners, their relationship with educators, and their purpose in the education system. This study aims to examine two main issues: how the essence of learners is understood from the perspective of educational philosophy, and how this viewpoint impacts the relationship between learners and the educational process. The type of research in this article is qualitative research with an educational philosophy approach. Data sources are obtained from literature studies on the works of classical to contemporary educational philosophy figures. Data collection techniques use documentation, while analysis is conducted through content analysis and philosophical interpretation. The results of the study indicate that learners in educational philosophy are viewed not merely as objects of learning, but rather as active, autonomous subjects who develop through interaction with values and life experiences. In addition, the philosophical perspective encourages the need to transform the relationship between educators and learners from an instructional relationship to a dialogical and humanistic one. The implications of these findings emphasize the need for a reorientation of the curriculum and educational approaches that are more student-centered as thinking and meaningful beings.